Innate defense capability of challenged primary bovine mammary epithelial cells after an induced negative energy balance in vivo - K. Danowski; D. Sorg; J. Gross; H.H.D. Meyer; H. Kliem (Czech Journal of Animal Science, 2012)
Negative energy balance (NEB), if followed by metabolic imbalance, is a common problem in high-yielding dairy cows frequently associated with inflammation of the mammary gland. After entering the teat canal, mammary epithelium is the first line of defense against a pathogen invasion. To investigate the effect of NEB on the innate host defense of the mammary epithelium, primary bovine mammary epithelial cell (pbMEC) cultures were generated by cell extraction of milk derived from energy restricted and control feeding cows. pbMEC were obtained from 8 high-yielding dairy cows affected by induced NEB in mid-lactation due to a reduction to 51 ± 2% of total energy requirement (restriction group) and from 7 control cows (control group). They were exposed to heat-inactivated Escherichia coli and Staphylococcus aureus for 24 and 72 h to investigate the influence of NEB on gene expression profiles of cytokines, chemokines, genes associated with apoptosis and antimicrobial peptides plus their receptors (AMPR) of the innate immune response. The immune challenge of pbMEC demonstrated an effect of immune capacity and NEB in 15 differential expressed genes. NEB induced a substantial up-regulation in restriction compared to control cells by trend in E. coli and a down-regulation in S. aureus exposed cells. Our investigations showed that the dietary-induced NEB in vivo influenced the immune response of pbMEC in vitro and altered the expression of immunological relevant genes due to a difference in energy supply. These results demonstrate that pbMEC are a suitable model for mastitis research, in which even effects of feeding regimes can be displayed.